Effect of humic and salicylic acid on potato vegetative area, yield and quality at two different irrigation levels - Maher dais; Hadia Hassan; Sawsan Suleiman (Al-Qadisiyah Journal of Pure Science, 2022)
Abstract: This study was carried out at Al-Hanadi Research Station -Agricultural Scientific Research Center in Lattakia during 2019-2020, to study the effect of foliar spray with different concentrations of humic acid (500, 1000 and 1500 ppm) and salicylic acid (50, 100 and 150 ppm) on Spunta potato plants at two levels of irrigation 40% and 80% of field capacity. The experiment included 14 treatments and 3 replicates for each one. It was designed with a complete randomization system. Results showed a decrease in vegetative surface area and yield kg/m2 at irrigation level 40% of field capacity, while  tubers content of proline and dry matter tubers increased. The highest tuber content of proline was in humic acid 1000 ppm at 40% of field capacity. At irrigation level 80% of field capacity, the treatment with salicylic acid 100 ppm showed the highest yield 4.09 kg/m2and the highest  tuber content of sugars   in  salicylic acid 100 ppm at the same irrigation level. Salicylic acid treatment 50 ppm gave also the highest vegetative surface area (2278) cm2.